Electrochemical oxidation of nitrite and the oxidation and reduction of NO2 in the room temperature ionic liquid [C2mim][NTf2]. - Broder, T; Silvester, D; Aldous, L; Hardacre, C; Compton, R (2007)
The electrochemical oxidation of potassium nitrite has been studied in the room temperature ionic liquid (RTIL) [C2mim][NTf2] by cyclic voltammetry at platinum electrodes. A chemically irreversible oxidation peak was observed, and a solubility of 7.5(+/-0.5) mM and diffusion coefficient of 2.0(+/-0.2)x10(-11) m2 s(-1) were calculated from potential step chronoamperometry on the microdisk electrode. A second, and sometimes third, oxidation peak was also observed when the anodic limit was extended, and these were provisionally assigned to the oxidation of nitrogen dioxide (NO2) and nitrate (NO3-), respectively. The electrochemical oxidation of nitrogen dioxide gas (NO2) was also studied by cyclic voltammetry in [C2mim][NTf2] on Pt electrodes of various size, giving a solubility of ca. 51(+/-0.2) mM and diffusion coefficient of 1.6(+/-0.05)x10(-10) m2 s(-1) (at 25 degrees C). It is likely that NO2 exists predominantly as its dimer, N2O4, at room temperature. The oxidation mechanism follows a CE process, which involves the initial dissociation of the dimer to the monomer, followed by a one-electron oxidation. A second, larger oxidation peak was observed at more positive potentials and is thought to be the direct oxidation of N2O4. In addition to understanding the mechanisms of NO2- and NO2 oxidations, this work has implications in the electrochemical detection of nitrite ions and of NO2 gas in RTIL media, the latter which may be of particular use in gas sensing.